A model of contributors to a trusting patient-physician relationship: a critical review using a systematic search strategy - Lerch, Seraina Petra; Hänggi, Rahel; Bussmann, Yara; Lörwald, Andrea (BMC primary care, 2024)
The lack of trust between patients and physicians has a variety of negative consequences. There are several theories concerning how interpersonal trust is built, and different studies have investigated trust between patients and physicians that have identified single factors as contributors to trust. However, all possible contributors to a trusting patient-physician relationship remain unclear. This review synthesizes current knowledge regarding patient-physician trust and integrates contributors to trust into a model.